Desempenho do ecossistema de inovação do setor de energia solar fotovoltaica - Cattelan, Verônica Dalmolin (2019)
Increasing complexity in the business environment, increasing competition and consumer demands, and the rapid development of technologies are changing the conditions in which companies operate and require improved management practices. Thus, the competitiveness of organizations is directly related to the ability to adapt to the oscillations of the environment in which they operate and the search for innovation has been configured as one of the key factors for competitiveness. To address this process of creating joint value, based on the concept of innovation ecosystem, this research proposes a modeling capable of measuring and evaluating the competitive performance of the innovation ecosystem actors of the solar photovoltaic sector, in the structural and business spheres. . Such a sector is growing exponentially worldwide, and this technical and commercial growth in photovoltaic solar power generation should be supported by energy management studies through decision support tools. To drive the growth of the solar photovoltaic sector, and in particular the Micro and Distributed Minigeneration segment, a number of economic, political, environmental and social factors must be present, mainly because the adoption of an innovation is a complex process. For this, a qualitative, quantitative, exploratory and descriptive research was conducted through a multicase study. For modeling development 58 performance indicators were raised. For this, the assumptions regarding the Key Performance Indicators (KPI) were used, as well as the methodological support in elements of the Analytic Hierarchy Process (AHP). The KPI were assigned to 36 Critical Success Factors and grouped into three Fundamental Points of View: Human Capital, Relationship Capital and Structural Capital. The collection instrument was applied to 17 actors in the photovoltaic innovation ecosystem and the respective global performance was returned to them, as well as the performance in each of the Fundamental Points of View that comprise competitiveness in this environment. To facilitate the collection, processing of data and updating of indicators and scales of assessment, a computational tool was also developed. With regard to contributions, this research can be considered as the starting point for identifying the factors that lead to the competitive success of the actors in the studied innovation ecosystem, in addition to allowing the measurement of the actors' performance. The replacement rate estimates allowed the visualization of the difference regarding the importance between the KPI selected for the modeling. The resulting values demonstrated greater importance for KPI: being a reference in innovation; be motivated to invest in photovoltaic technology; know the regulation of the activity sector and; know the technical quality references of the photovoltaic system. The results showed that the evaluated actors have the lowest levels of performance for Relationship Capital, suggesting a greater difficulty in the interdependence relationships between the actors in the ecosystem, which undermines the generation of competitive value among the stakeholders of the photovoltaic solar energy sector.